(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2022)
The increase of cadmium pollution over time is the result of an unbalanced fertilization process. The aim of this study was to quantify the concentration of cadmium in agricultural soils used for cocoa production in the Arenillas canton, province of El Oro, southwestern Ecuador. For the study, four sampling points were selected, triplicate samples for each point at depths of 0-10, 10-20, 20-30 cm were taken. The flame atomic absorption spectrophotometry (AAS) method was used to quantify cadmium. In addition, analyses of the physicochemical parameters of the soil and of the most used fertilizers were carried out to determine their influence on soil Cd. It was shown that there was a greater presence of cadmium at depths of 20-30 cm, with concentrations varying between 0.40-0.52 mg/kg of Cd, so it was concluded that this was mainly due to the contribution of cadmium by the used fertilizers.